Pelayanan Publik di Kantor Koordinator Pendidikan Kecamatan Taniwel dan Taniwel Timur Kabupaten Seram Barat - AHIYATE, NENGSI DOMINIKE; ROLOBESSY, MIKE J. (Patria Artha University, 2022)
This study aims to determine the level of public service at the Education Coordinator Office of Taniwel and Taniwel Timur Subdistricts, West Seram Regency, and to find out the obstacles and steps to optimize public services at the Education Coordinator Office of Taniwel and Taniwel Timur Districts, West Seram Regency. This research is a combination of quantitative descriptive using a qualitative approach. The subjects of this study were all service users of the Education Coordinator Office of Taniwel and Taniwel Timur Districts, West Seram Regency who needed public services. The data analysis of this study used the frequency value and the average score. Based on the results of the analysis, it is known that the level of public service at the Education Coordinator Office of Taniwel and Taniwel Timur Districts, West Seram Regency is in the B- or Good category with a note. This assessment is reviewed from 6 aspects, namely service policy, HR professionalism, infrastructure, public service information systems, consultation and complaints, and service innovation. The obstacles in public services at the Education Coordinator Office of Taniwel and Taniwel Timur Subdistricts, West Seram Regency, namely: The condition of employees who are generally still high school educated, lack of technological knowledge in employees due to lack of training, and limited facilities and infrastructure. The steps to optimize public services at the Education Coordinator Office of Taniwel and Taniwel Timur Subdistricts, West Seram Regency are to cultivate excellent service, increase supporting facilities, increase HR professionalism, and evaluate the results of satisfaction assessments with services.